Unraveling Reaction Formation in "The Haunting of Hill House" by Shirley Jackson - Viona Aprilia Sabilla; Prayudias Margawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to find out defense mechanism of Eleanor character in the novel The Haunting of Hill House by Shirley Jackson. The primary issue raised is how Eleanor character employs defense mechanisms, especially reaction formation to cope with her past traumas. This research focuses on identifying events from Eleanor’s past that contribute and trigger reaction formation in Hill House, a house where the characters attended as respondent. This study uses a descriptive qualitative method. The data consist of excerpts from the novel The Haunting of Hill House. The results reveal the forms of reaction formation shown by the character. These findings contribute to a better understanding of the connection between trauma and defense mechanisms in the characters. For example, Eleanor character manipulated her behavior while staying at Hill House, revealing a different side of herself to the other characters. This aligns with Freud’s theory of reaction formation. Eleanor character tried to hide her true feelings so that the other characters would not isolate her. This situation shows how people can use reaction formation as a defense mechanism to cope with their trauma or her psychological conflicts.